2014
DOI: 10.3171/2013.10.peds1345
|View full text |Cite
|
Sign up to set email alerts
|

Neurolysis alone as the treatment for neuroma-in-continuity with more than 50% conduction in infants with upper trunk brachial plexus birth palsy

Abstract: Object The debate addressed in this article is that of surgical treatment methods for a neuroma-in-continuity. The authors of this study chose to test the hypothesis that more severe nerve injuries, as distinguished by < 50% conduction across a neuroma-in-continuity, could be treated with neuroma resection and grafting, whereas less severe nerve injuries, with > 50% conduction across the neuroma, could be treated with neurolysis alone. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Most studies were completed in Europe, followed by three studies performed in Asia and South America . Three studies were conducted in the United States …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies were completed in Europe, followed by three studies performed in Asia and South America . Three studies were conducted in the United States …”
Section: Resultsmentioning
confidence: 99%
“…All studies are prone to selection bias by including a nonrandom sample of the NBPP population. Six studies included a surgery group, five included a slow recovery or severe group, and five included NBPP children referred to a tertiary center . In two studies the population was restricted to upper trunk lesions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31,32] A study of neurolysis alone in upper trunk brachial plexus neuroma-in-continuity revealed a functional improvement following neurolysis alone in cases where there was more than 50% conduction demonstrated intraoperatively across the nerve. [33] Opponents of neurolysis alone, however, warn of the risks of segmental revascularization and significant scar formation. [34] This has led to the development of techniques designed to prevent recurrent scarring such as wrapping the nerve in a variety of protective substances.…”
Section: Neurolysis Alonementioning
confidence: 99%